Undertaking a Diversity Mark application for Kent and Medway Medical School: A reflection on the process. - Bintley, Helen (Advanced Journal of Professional Practice, 2025)
This reflection describes what is involved in undertaking a University of Kent (UoK) Diversity Mark Award and what the implications are of undertaking such an application for individuals, teams and the wider University. The author will outline the principles and activities involved in the application for Kent and Medway Medical School (KMMS) modules as well as considering the benefits and challenges of applying. The author concludes by discussing future plans for expanding the reach of the award in a KMMS context.